Edoxaban and implantable cardiac device interventions: insights from the ENGAGE AF-TIMI 48 trial. Issue 2 (19th November 2018) - Steffel, Jan; Ruff, Christian T; Braunwald, Eugene; Hamershock, Rose A; Murphy, Sabina A; Nieminen, Markku; Lanz, Hans-Joachim; Mercuri, Michele F; Peterson, Nancy; Antman, Elliott M; Giugliano, Robert P
Abstract: Aims: Pacemaker, implantable cardioverter-defibrillator, and cardiac resynchronization therapy device implantations and generator changes are frequently performed in patients receiving direct oral anticoagulants. In an exploratory analysis, we investigated the outcome of patients undergoing such device procedures in the ENGAGE AF-TIMI 48 trial. Methods and results: During the trial, 1217 device procedures were performed in 1145 patients, with intervention dates available for 1203 procedures. Two hundred and twenty-five procedures (in 212 patients) were performed >30 days after study drug was stopped and are not included in the event analysis. For most interventions ( n  = 728, 74%), study drug was interrupted >3 days (median for the entire cohort: 5 days, interquartile range 0–11 days); 250 interventions were performed with ≤3 days study drug interruption. During the first 30 days after the procedure, six strokes/systemic embolic events (SEEs) (three each in the lower-dose edoxaban and warfarin arm) and one major bleeding event (in the lower-dose edoxaban arm) occurred; no stroke/SEEs or major bleeds occurred around the 295 device procedures in the higher-dose edoxaban arm. Two ischaemic and one major bleeding event occurred after the 288 device procedures performed with ≤3 days periprocedural interruption of study drug. Conclusion: In this first experience of patients undergoing device surgery with edoxaban, a low risk of ischaemic and bleeding events was observed during the first 30 days post-procedure. Our data are in line with current recommendations of no or only brief interruption of non-vitamin K antagonist oral anticoagulants prior to cardiac device surgery.